STRATEGI MGMP SEKOLAH MENENGAH PERTAMA DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI TENGAH BERBAGAI KENDALA : (Studi Kasus di Kabupaten Limapuluh Kota Provinsi Sumatera Barat) - Bambang Suwardi Joko (Jurnal Penelitian Kebijakan Pendidikan, 2020)
This study aims to i) obtain information on what efforts are carried out by MGMP with junior high school subjects in the district. Fifty Cities in order to be able to run to maximize teacher professionalism in the midst of constraints and limitations, ii) know the profile of the MGMP subject to SMP from funding, and activeness, iii) obtain information on the constraints and solutions carried out by the junior high school MGMP management, in facing limitations and obstacles. This study used a descriptive qualitative approach with a case study research design. Data collection techniques are non-participant open observation, semi-structured interviews and documentation studies. The data used in this study are primary data collected through clustered group discussion (DKT) and filling out a questionnaire by 14 heads / administrators of the MGMP. Data were analyzed using descriptive statistical techniques. The results of the study concluded that (i) the efforts made by MGMP with junior high school subjects included upholding the principle of kinship. The activities are always coordinating, and all problems are always decided together related to funds, location, materials and the existence of the narcissum, (ii) the profile of the MGMP subject to junior high school is mostly very active in holding meetings 12 times a year, as well as the percentage of active MGMP on average. average above 70 percent. The management also assured, whether there is assistance or not, the MGMP must continue to run with independent funds, (iii) the classic obstacles of the MGMP are always decided together, the working principle reflects the activities of "from, by and for the teacher".